Rapid Development of Intestinal Type Gastric Adenocarcinoma - Young S. Oh; Benson T. Massey (Case Reports in Gastroenterology, 2011)
Intestinal type gastric adenocarcinoma is felt to develop over a protracted time period through a series of defined steps. Several potential risk factors for the development of gastric cancer have been identified, including a family history of gastric cancer and Helicobacter pylori infection. We present the case of a patient with neither risk factor who progressed in a 14 month time frame from histologically normal gastric mucosa to early stage intestinal type gastric adenocarcinoma in the setting of diffuse gastric intestinal metaplasia and atrophic gastritis. This patient’s presentation conflicts with our current understanding of the development of intestinal type gastric adenocarcinoma.